Evaluation of La-Doped Mesoporous Bioactive Glass as Adsorbent and Photocatalyst for Removal of Methylene Blue from Aqueous Solution. (19th November 2015) - Li, Liying; Shi, Huanrui; Chen, Lu; Yuan, Qianxuan; Chen, Xi; Lin, Weijian
Abstract : A series of La-doped mesoporous bioactive glass (BG-La) materials with excellent biosafety and hypotoxicity have been prepared and tested as adsorbent. The study was aimed to evaluate the possibility of utilizing BG-La for the adsorptive removal of methylene blue (MB) from aqueous solution and test the adsorption and desorption behavior of this new material. The process parameters affecting adsorption behaviors such as pH, contact time, and initial concentration and the photocatalytic degradation of MB were systematically investigated. The result showed that BG-La had excellent removal rate ( R ) of MB, and BG-La showed better photocatalytic effect than undoped mesoporous bioactive glass (BG). Furthermore, the MB loaded BG-La was easily desorbed with acid solution due to its electronegativity and mesoporous structure. The result indicated that these materials can be employed as candidates for removal of dye pollutant owing to their high removal rate, excellent photocatalytic effect, desorption performance, and their reusability.